Controlling macromolecular structures towards effective antimicrobial polymers. (20th April 2015) - Ganewatta, Mitra S.; Tang, Chuanbing
Abstract: Drug resistance of pathogenic bacteria is a major global problem leading humanity towards a pre-antibiotic era. Decline in the discovery of novel antibiotics and the lack of a resilient platform to develop novel antimicrobial agents worsens the situation. Amphiphilic antimicrobial polymers, which have roots coming from antimicrobial peptides, show promise as potent antimicrobials having low susceptibility for developing resistance, unlike small molecular antibiotics. This feature article highlights recent advances in the fabrication of membrane-active antimicrobial polymers. The design of various types of macromolecular architectures with control of structural parameters such as hydrophobicity/hydrophilicity balance, molecular weight, and ionic groups will be emphasized in order to achieve strong antimicrobial activities while minimizing toxicity to mammalian cells. Advanced polymeric assemblies with well-defined nanostructures including core/shell shaped nano-objects and polymeric vesicles are also discussed. Lastly, current challenges and future directions in the field of antimicrobial polymers for ensuing practical biomedical applications are presented. Graphical abstract: Highlights: Summarized recent development on macromolecular architectures towards efficient antimicrobial agents against various microorganisms. Capitalized macromolecular assembly and nanoparticles as new vehicles to fight against resistant bacteria. Conceptualized future design principles and new directions in the field of antimicrobial polymers.